Analysis of Factors Influencing Poverty in The Special Region of Yogyakarta - Sitorus, Stefani Angela; Ashar, Khusnul (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study analyzes the factors influencing poverty in the Special Region of Yogyakarta Province (DIY). Among the five provinces on the island of Java, DIY is recorded as the poorest. This study incorporates health and education as independent variables, unemployment as a mediating variable, and poverty as the dependent variable. This quantitative research employs secondary data from BPS, covering five districts/cities in DIY Province from 2010 to 2020. and applies the multiple linear regression method using panel data analysis. The results reveal that health has a positive and significant effect on unemployment, while education has a negative and significant effect on unemployment. Furthermore, unemployment positively influences poverty. In addition, unemployment mediates the relationship between health and poverty negatively and significantly, as well as mediates the relationship between education and poverty positively and significantly. This study highlights that improvements in health and education must be accompanied by job creation initiatives to optimize their impact on poverty reduction.